Why Saudi Learners of English Prefer using Bilingual Paper Dictionary? Facts and Opinions (Global Journal of Human-Social Science, 2017)
This study investigated the real reasons behind the preference of Saudi learners of English through using random sample The sample included 30 postgraduate and undergraduate students who were studying in both universities of Salford and Manchester based in Manchester in the UK in the academic year of 2015 The study employed two research instruments for the purpose of data collection namely questionnaire and interview The study discovered two key reasons which made the Saudi students prefer this kind of dictionaries The first one is the usage of native language of learner The Second one because of the rich informative content which can provide more details regarding the vocabulary such as examples collocations grammatical syntactic and phonological aspects contrary to the electronic dictionaries which only provide the meaning of the new words without giving any further details for clarification The results obtained also confirmed the fact of using bilingual paper dictionary for translation tasks
Keywords: bilingual dictionaries; paper dictionaries; Saudi learners; reasons